Evaluation of tourism development as the impact of community satisfaction - Sari Lestari Zainal Ridho; Pitaya Pitaya; Habsah Binti Haji Mohamad Sabli (Jurnal Pariwisata Pesona, 2022)
This study aims to examine the community satisfaction, which consists of public service satisfaction, environmental satisfaction, recreational opportunity satisfaction, economic satisfaction, community involvement, and social opportunities and medical services satisfaction, has an effect on the support of tourism development in Indonesia. This purpose was set since the sustainability of tourism development is something important, so it requires support from the community. The data used are primary data collected through a survey in the form of a questionnaire. The population in this study were the people of Indonesia, while the sample was determined by using a simple random sampling technique. The analysis technique used is PLS-SEM considering the suitability of these techniques with research objectives. The findings of this study based on the results of data processing are that environmental satisfaction, economic satisfaction, community involvement, and social opportunities have an effect on tourism development support in Indonesia, while public service satisfaction, recreational opportunity satisfaction, and satisfaction with medical services have no effect.